Impact of Planting Technologies in Cash Flow Producer Sugarcane - Moraes Farinelli, Juliana Borba de [UNESP]; Lopes Santos, David Ferreira (Fundacao Pedro Leopoldo, 2017)
The technological changes in sugarcane production, in order to meet environmental and social requirements, have brought to the rural producer a context of productivity declines and in the productive cycle of the crop, which, together with the oscillations of the sugar and ethanol sector, demand both the development of new productive technologies As well as instruments that assist the rural producer in the decision making regarding the use of these. In this sense, the present report aims to analyze the impact of new technologies of sugarcane planting on the cash flow of a rural property, located in the municipality of Jaboticabal / SP. It was verified that the two new technologies of planting analyzed although they provide an increase in productivity, only one presents a positive result in relation to the other modes of planting. However, it is inferred that the new technologies of planting do not give to enable the cultivation of the sugar cane for small and medium producers of the region.
Keywords: Meiosi; pre-budded seedlings; sugarcane; point of equilibrium